Progress Report to The IMFC On the Activities Of The Independent Evaluation Office Of The IMF : October 9, 2020. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2020)
The IEO is advancing its work program while adapting to the challenges from the COVID-19 pandemic. While evaluation is not part of the frontline response that has dominated IMF activity over the past six months, independent evaluation remains a key function for learning from experience and drawing lessons for the Fund as it focuses on meeting members' urgent and evolving needs. Since April, IEO engagement with the Executive Board has resumed, including formal discussion of the recently completed evaluation of IMF Advice on Capital Flows and an informal seminar on Bank-Fund collaboration on climate issues. Work continues on evaluations of adjustment and growth in IMF-supported programs and IMF engagement with small states, and a new evaluation is being launched on IMF capacity development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Capacity Development Activity; IMF Engagement; IMF Pilot Initiative; PP